Spatial Distribution Of Microplastics In Sediments Of The Karangsong Mangrove Ecotourism Area, Indramayu - Fitriani; Zahidah Hasan; Roffi Grandiosa; Mochamad Candra Wirawan Arief (CV. AFDIFAL MAJU BERKAH, 2026)
Karangsong Mangrove Ecotourism Area is an area in Indramayu Regency that has various activities such as tourism, fishing and anthropogenic. These activities produce waste such as plastic which is then fragmented into small particles (microplastics). This research aims to determine the distribution and abundance of microplastics caused by different activities around the Karangsong Indramayu Mangrove Ecotourism area. The environmental factors used in this research are temperature and pH taken in situ and current data obtained from the Copernicus marine. Sediment samples were taken using a piston core once a week for one month. Furthermore, laboratory tests were carried out to see the abundance and characteristics of microplastics. The data that has been obtained is then tested with oneway ANOVA with a significance level of 5%. The highest abundance of microplastics was found at Station 3 (Beach) with a concentration of 15.87 ± 1.05 particles/g and the lowest abundance was identified at Station 1 (Ecotourism Area) with a concentration of 1.25 ± 0.04 particles/g. The dominating characteristics at each station are the types of Fragments and Films, yellow and transparent colors, and microplastics <1mm in size.